The Analysis of Students’ Ability in Speaking by Using Information Gap Strategy at the Eighth of SMP Negeri 1 Gido in 2022/2023 - Pintariani Lase; Nursayani Maru'ao; Yasminar Amaerita Telaumbanua; Elwin Piarawan Zebua (Edumaspul: Jurnal Pendidikan, 2023)
Speaking is one of the important skills in English besides listening, reading and writing. It is important because speaking is always used in daily activities. People can convey their opinions, ideas, and express their expressions or feelings to others. Speaking is very important in language learning because it can make students active in communicating with others and giving opinions or ideas in the teaching-learning process. The purpose of this research is to analyze students' speaking ability by using Information Gap strategy in class VIII of SMP Negeri 1 Gido. This research uses qualitative research which emphasizes understanding problems in social life based on reality conditions, or real natural settings that are holistic, complex, and detailed. The sample size was 34 students in class VIII-B. while the data collection techniques were observation, interview, and documentation. the research results from the test were 9 students classified as poor, 19 people classified as good. The percentage from highest to lowest is: Excellent (0%) with a frequency of 0, good (71,4%) with a frequency of 25, fair (26.4%) with a frequency of 9, poor (0%) with a frequency of 0, and very poor (0%) with a frequency of 0. The results of speaking ability in using the information gap strategy of class VIII-B students fall into the good and sufficient category, it is known that 9 students scored 41-60, 25 students scored 61-80, they are at a good level which is around 61-80, meaning that their average score is 68.67.